Influence of polarization of semiconductor lattice on its optical vibration spectrum - Severin, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Considered in this paper are optical spectra of crystal lattice vibrations in
semiconductor solid solutions, which have two vibration bands depending on solution
composition. It has been shown that this dependence for the vibration spectrum is
conditioned by polarization of this lattice, which is not taken into account by the
traditional theory for the optical spectrum of lattice vibrations.